KOMPETENSI IBU DALAM PENDIDIKAN LITERASI KEUANGAN ANAK SEJAK DINI Di KELURAHAN SEMOLOWARU SURABAYA - Ani Suhartatik; Cicilia Erna Susilawati; Arini Arini; Shanti Shanti (PeKA: Jurnal Pengabdian Kepada Masyarakat, 2022)
This community service aims to provide insight to the residents of Semolowaru Village surabaya on the importance of increasing maternal competence in children's financial literacy from an early age The method of devotion applied in the form of 1) discussion and sharing of semolowa village mothers with the hope of this activity mothers get insight knowledge about financial management in accordance with the stages of child development, 2) training in the development of literacy learning methods for children. This training is expected to modify according to the characteristics of children so that children are able to apply financial management according to their age and development. Results from the implementation of activities are monitored and evaluated based on the results of questionnaires. The questionnaire was compiled by Tim Abdimas to be filled out by 20 participants whose results showed that 80% of the mothers of abdimas activity participants were able to absorb the concepts of financial management for children submitted by the abdimas team and were able to implement them to their children. This shows that in general, abdimas activities have a real impact on increasing the mother's knowledge about financial management for children